Social media and public relations : fake friends and powerful publics - Motion, Judy.; Heath, Robert L. (Robert Lawrence), 1941-; Leitch, Shirley, 1960- (New York : Routledge, 2016)
"Social media has had a profound, and as yet not fully understood impact on public relations. In the 24/7 world of perpetually-connected publics, will public relations function as a dark art that spins (or tweets) the truth for credulous publics? Or must public relations be reconceptualized under the full glare of the internet and the expectations of increasingly powerful publics? The purpose of this book is to examine the role of public relations in social media through an exploration of the myriad ways that social media is reshaping its core concepts and activities. In particular, it examines the dichotomies of fake and authentic, powerful and powerless, meaning and meaningful. It also examines the key transgressions committed by practitioners: the paucity of digital literacy, a widespread lack of understanding of the norms of social media, a naivety about the corporate identity risks, and a prevalent emphasis on spin and persuasion rather than on authentic engagement. This challenging and fascinating book will be of interest to all students, researchers and practitioners in Public Relations, Media and Communication Studies"--
Machine generated contents note: 1. Identify the problems: social media and public relations -- 2. "Don't do anything stupid": social media affordances, policies, and governance agendas -- 3. Create yourself: corporate identity for interconnected publics -- 4. Speak the truth: transparency, power/knowledge, and authenticity -- 5. Engage: one-way, two-way, and every-way -- 6. Connect creatively: worlds, identities, and publics as content production and co-production -- 7. Engage critically: activist power -- 8. Protect yourself: issues of privacy and regulation -- 9. Know your risks: a collective orientation -- 10. Navigate the issues: situating power/knowledge within public relations -- 11. Reshape policy: public -- private clashes and collaborative dialogue -- 12. Conclusion.
Includes bibliographical references and index.
Keywords: Social media; Public relations